2023
DOI: 10.1002/elan.202200497
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and fluorimetric pH sensing using polydiacetylene embedded within PVC‐PCL nanofibers

Abstract: The applicability of model polydiacetylenes (PDAs) in hydrogen ions sensitive optodes was tested. Nanofibers mats were electrospun using a mixture of polyvinyl chloride (PVC) and polycaprolactone (PCL) together with 10, 12‐tricosadiynoic acid (TCDA) or 10,12‐pentacosadiynoic acid (PCDA). After the polymerization the mats were applied in colorimetric and fluorimetric pH sensors. The PDAs were formed by photopolymerization with a UV lamp (254 nm), resulting in a change of mats color from white to dark blue. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The prepared sensors were studied in two readout modes: colorimetric using a smartphone camera and fluorimetric one. Their experimental results demonstrated that both readout modes could be successfully used for pH sensing with proposed nanofibrous mats in the range of pH close to the physiological pH range 11 . In another study, Park et al produced a textile‐based colorimetric sensor for acidic gas detection using rhodamine dye with improved thermal properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared sensors were studied in two readout modes: colorimetric using a smartphone camera and fluorimetric one. Their experimental results demonstrated that both readout modes could be successfully used for pH sensing with proposed nanofibrous mats in the range of pH close to the physiological pH range 11 . In another study, Park et al produced a textile‐based colorimetric sensor for acidic gas detection using rhodamine dye with improved thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental results demonstrated that both readout modes could be successfully used for pH sensing with proposed nanofibrous mats in the range of pH close to the physiological pH range. 11 In another study, Park et al produced a textile-based colorimetric sensor for acidic gas detection using rhodamine dye with improved thermal properties. They investigated the sensitivity, durability, and reversibility of the fabricated textile sensors and showed that the sensor they fabricated could be a promising candidate for practical sensor applications.…”
mentioning
confidence: 99%